Managing delays in open pit shovel-truck systems – A case study - Temeng, V.A.; Kukula, J.K. (UMaT, 2010)
Delays are frequently encountered on a daily basis in open pit shovel-truck operations. A greater portion of these delays which are avoidable or reducible to the barest minimum if well managed can significantly reduce shovel-truck cycle times and increase utilisation. The traditional approach to analyzing delay data is by frequency plots categorized by type of delay and does not present the data in a format which facilitates management of the delays. This paper uses log dispersion plotting approach to analyse delay data from open pit shovel truck operations at Goldfields Ghana Ltd., Tarkwa Mine. Delay types were categorised into delay codes to determine which ones were acute, chronic or a combination of both. The delay codes which were critical to the reduction of delays and improvement of shovel-truck utilization were prioritised.
Keywords: Open pit; Shovel-truck operations